(3efXheI CSeGA Gddg GdMSfis - (3GdnYnOhj, CHh GdHQcGJ, GdnqOrQpOjQ, CMeO Hf eMeO Hf CMeO, J(B1201(3g`s ((3eMeO Hf SYO GdOjf GdCSOj GdTGaYj GdbGOQjs)
(3ChdgG (B:s
(3JHGQcJ jG Gddg, QH dc GdKfGA HCSeGFc GdMSfi hCSQGQgG GdJj CbeJ HgG GdCchGf ef MVQI GdZfG afOYhc jG Gddg jG eHOY GdhQis
(3BNQgG (B:s
(3ajGQH fhQfG HCfhGQ SQg haj Sdcg GfXefG hHGddWa MafG hHdZg aj GdOGQjf cd eQGOg hCJHGYg jG SGeYG dOYGFfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 244s
(3eYLe GdeDdajf(B: 1 / 242s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs